Role of Near-Infrared Spectroscopy in Monitoring the Clinical Course of Asphyxiated Neonates Treated with Hypothermia - Farag, Marwa Mohamed; Khedr, Ahmed Abd El-Halim Abd El-Raziq; Attia, MennattAllah Hassan; Ghazal, Hesham Abd EL-Rahim (American Journal of Perinatology, 2021)
Objective Hypoxic-ischemic encephalopathy (HIE) affects millions of newborns annually, especially in low-resource settings. Real-time monitoring of hypoxic-ischemic brain damage is urgently needed for assessment of severity and management of neonates with birth asphyxia. Aim of the work is monitoring of near-infrared spectroscopy (NIRS)-measured cerebral regional oxygen saturation (cRSO2) and cerebral fractional tissue oxygen extraction (FTOE) in neonates after birth asphyxia in relation to their clinical course.Study Design Forty asphyxiated-term and near-term neonates with mild to severe HIE admitted at neonatal intensive care unit of Alexandria University Maternity Hospital from March to October 2019, received therapeutic hypothermia (TH) and had continuous NIRS monitoring of cRSO2 for 72 hours. Infants were categorized into HIE with seizing and nonseizing groups, and abnormal and normal magnetic resonance imaging (MRI) groups.Results Clinical seizures (CS) occurred in 15 (37.5%) of HIE neonates and 13.3% of them died (n = 2). In the current study, significantly higher cRSO2 and lower FTOE values were found in the seizing infants as compared with nonseizing group (p < 0.001). NIRS-measured day 2-cRSO2 and day 1-FTOE were associated with CS in newborns with HIE and day 1-cRSO2 and FTOE were associated with abnormal MRI at 1 month of age. cRSO2 values were found to correlate positively with initial Thompson score especially in days 1 and 2. Further, neonates with CS were more likely to have MRI abnormalities at follow-up.Conclusion NIRS measures may highlight differences between asphyxiated neonates who develop CS or later MRI abnormalities and those who do not.Key Points
Keywords: hypoxic-ischemia; therapeutic hypothermia; clinical seizures; near-infrared spectroscopy; cRSO2; FTOE